2008
DOI: 10.1007/s10995-008-0409-2
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Pregnancy-Related Drinking Reduction

Abstract: Significant racial differences in pregnancy-related drinking reduction are evident, and may help explain racial disparities in FAS. Results suggest that more targeted efforts are needed to meet the national goals of preventing alcohol-exposed pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 18 publications
3
27
1
Order By: Relevance
“…The previously described cessation and reduction patterns are also found among women with unintended pregnancies (Hellerstedt et al, 1998, Kost et al, 1998, Pirie et al, 2000, Johnson et al, 1987, Tenkku et al, 2009, Terplan et al, 2013). There has also been substantial research examining predictors of alcohol use among pregnant women, including in income and race/ethnicity subgroups (Chambers et al, 2005, Tenkku et al, 2009, Pirie et al, 2000, Harrison and Sidebottom, 2009, Chasnoff et al, 2005, Johnson et al, 1987, Hellerstedt et al, 1998, Kost et al, 1998, Ethen et al, 2009).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…The previously described cessation and reduction patterns are also found among women with unintended pregnancies (Hellerstedt et al, 1998, Kost et al, 1998, Pirie et al, 2000, Johnson et al, 1987, Tenkku et al, 2009, Terplan et al, 2013). There has also been substantial research examining predictors of alcohol use among pregnant women, including in income and race/ethnicity subgroups (Chambers et al, 2005, Tenkku et al, 2009, Pirie et al, 2000, Harrison and Sidebottom, 2009, Chasnoff et al, 2005, Johnson et al, 1987, Hellerstedt et al, 1998, Kost et al, 1998, Ethen et al, 2009).…”
Section: Introductionsupporting
confidence: 61%
“…There has also been substantial research examining predictors of alcohol use among pregnant women, including in income and race/ethnicity subgroups (Chambers et al, 2005, Tenkku et al, 2009, Pirie et al, 2000, Harrison and Sidebottom, 2009, Chasnoff et al, 2005, Johnson et al, 1987, Hellerstedt et al, 1998, Kost et al, 1998, Ethen et al, 2009). However, literature on alcohol use patterns and risk factors among women with unwanted pregnancies is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the women in this study were African American, which may explain the low reported levels of alcohol use at baseline, as well as the larger percentage of African American women who were not eligible for the study (78.9%) compared to those eligible (59.5%). But heavy or binge drinking African American women are significantly less likely to reduce drinking or binging after becoming pregnant when compared to White women (Tenkku, Morris, Salas, & Xaverius, 2009). In addition, the CDC Fetal Alcohol Syndrome Surveillance Network (FASSNet) reported FAS rates to be highest for black and American Indian/Alaska Native children (Miller et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…African American women, in particular, may be less likely to reduce binge drinking (four or more drinks on one occasion) during pregnancy. 9 Data from the 2007-2008 National Survey on Drug Use and Health 7 suggest that 10% of African American pregnant women report binge drinking in the past month; this is up from 6% in 2005-2006 and is higher than for pregnant women overall, regardless of race or ethnicity (4.5% in 2007-2008).…”
Section: Introductionmentioning
confidence: 99%